2010
DOI: 10.1007/s10551-010-0461-x
|View full text |Cite
|
Sign up to set email alerts
|

Alliances Between Brands and Social Causes: The Influence of Company Credibility on Social Responsibility Image

Abstract: company expertise, company trustworthiness, functional fit, image fit, altruistic attributions, CSR image,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
154
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(181 citation statements)
references
References 86 publications
9
154
0
8
Order By: Relevance
“…The vast majority of previous studies considered a consumer to be a passive receiver of information about CSR efforts. High company-cause fit makes a consumer think less and enables more efficient information processing [20], excluding situations when corporate behavior is hypocritical [18]. The research findings of this paper complement past studies, as they indicate that a consumer can be an active receiver of CSR information and rationally evaluate companies and their socially responsible activities-that is, he or she recognizes the synergic effect of high corporate involvement in a congruent not-for-profit organization (or social cause) and derives value from this effect (as it is manifested by more favorable responses to a company and its activities).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The vast majority of previous studies considered a consumer to be a passive receiver of information about CSR efforts. High company-cause fit makes a consumer think less and enables more efficient information processing [20], excluding situations when corporate behavior is hypocritical [18]. The research findings of this paper complement past studies, as they indicate that a consumer can be an active receiver of CSR information and rationally evaluate companies and their socially responsible activities-that is, he or she recognizes the synergic effect of high corporate involvement in a congruent not-for-profit organization (or social cause) and derives value from this effect (as it is manifested by more favorable responses to a company and its activities).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Alcañiz, Cáceres, and Perez [20] find that corporate competence in managing social activities is evaluated on the basis of the company-cause fit, that is, if a company partners with a highly congruent NPO, a consumer is likely to consider the company to be competent in its CSR efforts. However, if a company cooperates with an unrelated NPO, consumers may conclude that it has no competence in addressing a specific social problem.…”
Section: The Moderating Role Of Company Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…For primary stakeholders, who have a direct relationship with a company [10], the company's reputation is mostly based on the degree to which the company is willing and able to fulfill the promises it makes to these stakeholders, either explicitly or implicitly [13]. For example, in a corporate social responsibility setting, Alcaniz et al [1] argued that the credibility of a company is key for reducing the tension between company and consumers. Consumers use company credibility as a means to judge and decrease their initial skepticism about the company.…”
Section: Corporate Reputationmentioning
confidence: 99%
“…The authors demonstrated the positive association between fit and favorability toward the event sponsor in response to sponsorship. Likewise, a number of congruent sponsorships supported its influence on a positive attitude toward the sponsor [77][78][79][80].…”
Section: Brand-cause Sponsorship Congruence Favorability Toward the mentioning
confidence: 97%